Potency of injectable hydroxyapatite chitosan (ihac) scaffold for rabbit femoral condyle defect regeneration - Paper Withdrawn - ENDANG W BACHTIAR,; DEWI F SUNIARTI,; NADIA D FADHILAH,; RAHMI ULFIANA,; BASRIL ABAS, (International Journal of Pharma and Bio Sciences, 2017)
Objective of this study is to evaluate the effect of Injectable Hydroxyapatite Chitosan Scaffold (IHAC) for rabbit femoral condyle bone regeneration by assessing its histological view. The experiment was conducted in New Zealand White Rabbits. Injectable Hydroxyapatite Chitosan Scaffold (IHAC) scaffold was transplanted into the femoral defect which had been prepared. Bone regeneration was analyzed histologically using Modified Salkeld Histological Scoring four weeks postoperatively. The results indicate that cortical bone fusion occurred better in the treated rabbit compared to control rabbit. In the treated rabbit, active osteoblast lined in the peripheral of mature bone. Cortical bone has underwent complete maturation. Control rabbit still showed the presence of hematoma and fibrocartilage that indicated earlyphase of bone regeneration. In conclusion, Injectable Hydroxyapatite Chitosan (IHAC) scaffold is potential for treatment of bone defect by guiding the host response to regenerate the bone tissue.